Orbital torque switching of room temperature two-dimensional van der Waals ferromagnet Fe3GaTe2 - Delin Zhang; Heshuang Wei; Jinyu Duan; Jiali Chen; Jiaxin Chen; Dongdong Yue; Wanxi Gong; Pengfei Liu; Yuhe Yang; Jinlong Gou; Junxin Yan; Kun Zhai; et al. (Nature Communications)
Abstract Efficiently manipulating the magnetization of van der Waals (vdW) ferromagnets has attracted considerable interest in developing room-temperature two-dimensional (2D) material-based memory and logic devices. Here, taking advantage of the unique properties of the vdW ferromagnet as well as promising characteristics of the orbital Hall effect, we demonstrate the room-temperature magnetization switching of vdW ferromagnet Fe3GaTe2 through the orbital torque generated by the orbital Hall material, Titanium (Ti). The switching current density is estimated to be around 1.6×106 A/cm2, comparable to that achieved in Fe3GaTe2 using spin-orbit torque from spin Hall materials (e.g., WTe2, and TaIrTe4). The efficient magnetization switching arises from the combined effects of the large orbital Hall conductivity of Ti and the strong spin-orbit correlation of the Fe3GaTe2, as confirmed through theoretical calculations. Our findings advance the understanding of orbital torque switching and pave the way for exploring 2D material-based orbitronic devices.